Isolation and Characterization of Bromelain (BML) Proteases from Ananas cosmosus an asset to Cancer Chemotherapy - G, Swaroop; Viswanathan, Geeta (International Journal of Pharmacology and Toxicology, 2013)
Chemo impediment impels the quest for moreover single targeted or brew of multi-targeted agents. Bromelain, potential agent in this regard, is a pharmacologically active compound, present in stems and fruits of Ananas cosmosus, endowed with anti-inflammatory, anti-invasive and anti-metastatic properties. Bromelain is a complex or proteolytic enzymes. These proteolytic enzymes are paraphernalia that promise an impressive number of medical and therapeutic uses, particularly as anti-tumour agents. The purpose of this study was to develop a lead range of BML extraction process. The purification of the enzyme was carried out by precipitation and by chromatography techniques. Further, the drying of chromatographically purified fraction was carried out in freeze dryer and spray dryer. The activity was expressed in terms of casein digesting units (CDU). The BML extract of higher purity was obtained from the fruit and stem using ion exchange chromatography. The elution competence in chromatographic purification was obtained in the range of 90%. Bromelain thus obtained was subjected to spray and freeze drying.  The BML was extracted using stem yielded a total protein content of 242.6 mg/mL with the proteolytic activity of 878.14 GDU/mL. The extracted Bromelain was characterized using the standard spectroscopic techniques such as IR Spectroscopy, UV-Spectroscopy, LCMS and PXRD to understand the structure of the lead molecule acting on the cancer cells.